Išeivijos spauda Lietuvoje per penketą sovietinio draudimo dešimtmečių - Vėlavičienė, Silvija (Knygotyra, 2005)
The second Soviet occupation (1944-1990) forced a significant part of the intelligentsia into exile to the West. In 1945, not only the publishing of Lithuanian books but also newspapers and magazines was launched in DP (Displaced Persons) camps in Germany. This kind of press was labeled by Lithuanian authorities as a weapon of hostile ideology. From the release of the very first publications, the Lithuanian exile press was under the watchful supervision of Soviet ideological and repressive institutions, as it served as a primary source reflecting the life and activities of emigrants or so-called people’s enemies. Meanwhile, these publications were kept secret from the public. Nearly 50 years of the Soviet ban on exile press can be compared with the Lithuanian press ban at the end of the 19th century and the beginning of the 20th century pursued by Tzarist rule. It was only since the 1950s that emigrants’ publications were stored in so-called "special preservation" departments of the greatest libraries of Lithuania. Strict directions for use restricted access to this kind of information. Meanwhile, the staff of the Press and Information Department of the Ministry of Foreign Affairs compiled and published exile press reviews in Lithuanian periodicals, providing their commentaries on the books and periodicals that were inaccessible to Lithuanian citizens. However, the reviews presented an extremely negative coverage of emigrant life. Irrespective of the ideological bias of the reviews, the public had an opportunity to get some information, though distorted and ideologically committed. Despite exceptionally strict measures taken on shipment control, withdrawal of books from parcels from abroad, and the confiscation of books from comers, since the 1950s, some Lithuanian exile publications appeared in private collections. This article deals with the illegal ways the exile press found its way into Lithuania. Based on numerous pieces of evidence, the article covers the dissemination of exile publications in society and their influence on their readers. The issue of Lithuanian emigration institutions’ standpoint on relations with occupied Lithuania is also widely discussed. The article presents two different views. Some took the position that any relations with organizations in occupied Lithuania were impossible. While others, particularly the organization "Santara-Šviesa" (an active participant of which was the incumbent President of the Republic of Lithuania, Valdas Adamkus), promoted the slogan "Face to Lithuania." "Santara-Šviesa" urged all emigration organizations to extend official contacts with Lithuania through the community "Tėviškė." The community, established by Soviet institutions for relations with nationals abroad, was under the strict control of national security organizations and was commanded from Moscow. However, it was the only legal way contributing to communication between emigrants and people of culture in Lithuania. Meanwhile, much effort was made to disseminate emigrant publications in Lithuania through other unofficial means since the publications served as an open window to a free world in an occupied country. The main event, which marked the beginning of cultural infiltration by emigrant representatives, was the journey of junior Lithuanian emigrant basketball players and the accompanying delegation to Lithuania, during which particularly large numbers of emigrant publications were brought and distributed. The Lithuanian exile press underwent a difficult journey to free itself from censorship and suppression. The restrictions and bans on the exile press were lifted only in July 1989, marking the end of a press ban that lasted nearly five decades.